(untitled) (American International Journal of Business and Management Studies, 2022)
In this modern era, healthcare services are provided through technology, one of which is m-health apps. As a developing country, Bangladesh pursues to offer healthcare facilities to its citizen by using modern technology. However, IT adoption is different among younger and older generations, and several factors impact the adoption intention. This research aims to investigate determinants influencing elderly citizens of Bangladesh to adopt m-health apps. This study applies PLS (Partial Least Squares) statistical technique based on Structural Equation Modeling (SEM) to achieve research objectives. A quantitative research methodology approach was adopted, and a structured questionnaire was disseminated to the 112 target respondents. Purposive random sampling technique was used in this study. The underpinning theory used in this research endeavor is the UTAUT model (Unified Theory on Acceptance and Use of Technology), incorporating several variables such as the quality of m-health apps, perceived risk, and cost. The findings demonstrate that social influence and app quality have a significant positive impact on older people’s willingness to adopt m-health apps. In addition, the behavioral intention of users and actual usage behavior have a significant positive association. By extending the UTAUT model with some rationally related variables, this research has contributed to the ICT of the healthcare profession. M-health app providers need to consider improving the features of apps as the quality of apps is regarded as a critical criterion for users. JEL Classification Codes: G91, F14, L11.